Quito’s Archaeological Heritage Protection: The “Delimitación de Áreas Arqueológicas del Bloque Quito” Project as a Case of Study - Montalvo, Carlos; Mosquera, Andres; Dyrdahl, Eric; Rivera, Valeria; Solines, Santiago; Gracia Riofrío, Maria; Granja, Gabriela (Ex Novo: Journal of Archaeology, 2021)
This work aims to outline and discuss the challenges and issues related to the protection of archaeological sites in urban contexts from an interdisciplinary approach, focusing on the collaboration and regulation between academia, consultants, local government offices and citizens. To achieve this objective, a team formed by archaeologists, geographers, and lawyers, coordinated and financed by a local government office (Municipality of Quito), was formed to develop tools to incorporate in the city’s cadastral map and draft specific legislation to regulate the land use in archaeologically sensitive areas. GIS (geographic information system) tools were applied to collect the geographical data (generation of an archaeological map) of the sites and compared with Quito’s cadastral data. The drafted law also pretends to raise awareness of landowners, construction companies, and the broader community, providing them with information about the properties located in archaeologically sensitive areas and establishing channels of dialogue between the relevant parties that will lead to the development of research projects in sensitive areas prior to their destruction.